Developing Novel Anthelmintics: The Stability Of Cysteine Proteinase Activity In A Supernatant Extract Of Papaya Latex - Fadlul Azim Fauzi Mansur; W. Luoga; J.M. Behnke; D.J. Buttle; I.R. Duce; M.C. Garnett (Cell press, 2024)
Indexed by Scopus